Important issues to be considered in developing fuzzy cognitive maps - Schizas, Christos N.; Papaioannou, Maria; Neocleous, Costas (My University, 2011)
The formalism of fuzzy cognitive maps as used for the modeling of various dynamical systems is presented with a critical point of view. Various issues related to terminology, concepts, sensitivities, time dependence, iteration procedures, and stability, are systematically considered with critical mind, aiming at making the overall system models be more realistic and useful, and to initiate discussions that can lead to clarifications and to uniformities. Emphasis is given to applications in social, political, economic and engineering systems.
Keywords: Fuzzy cognitive maps